Microglia Loss and Astrocyte Activation Cause Dynamic Changes in Hippocampal [18F]DPA-714 Uptake in Mouse Models of Depression - Guo, Jiamei; Qiu, Tian; Wang, Lixia; Shi, Lei; Ai, Ming; Xia, Zhu; Peng, Zhiping; Zheng, Anhai; Li, Xiao; Kuang, Li (Frontiers in Cellular Neuroscience, 2022)
Major depression is a serious and chronic mental illness. However, its etiology is poorly understood. Although glial cells have been increasingly implicated in the pathogenesis of depression, the specific role of microglia and astrocytes in stress-induced depression remains unclear. Translocator protein (TSPO) has long been considered a marker of neuroinflammation and microglial activation. However, this protein is also present on astrocytes. Thus, it is necessary to explore the relationships between TSPO, microglia, and astrocytes in the context of depression. In this study, C57BL/6J male mice were subjected to chronic unpredictable stress (CUS) for 5 weeks. Subsequently, sucrose preference and tail suspension tests (TSTs) were performed to assess anhedonia and despair in these mice. [18F]DPA-714 positron emission tomography (PET) was adopted to dynamically assess the changes in glial cells before and 2, 4, or 5 weeks after CUS exposure. The numbers of TSPO+ cells, ionized calcium-binding adaptor molecule (Iba)-1+ microglial cells, TSPO+/Iba-1+ cells, glial fibrillary acidic protein (GFAP)+ astrocytes, TSPO+/GFAP+ cells, and TUNEL-stained microglia were quantified using immunofluorescence staining. Real-time PCR was used to evaluate interleukin (IL)-1β, IL-4, and IL-18 expression in the hippocampus. We observed that hippocampal [18F]DPA-714 uptake significantly increased after 2 weeks of CUS. However, the signal significantly decreased after 5 weeks of CUS. CUS significantly reduced the number of Iba-1+, TSPO+, and TSPO+/Iba-1+ cells in the hippocampus, especially in the CA1 and dentate gyrus (DG) subregions. However, this intervention increased the number of GFAP+ astrocytes in the CA2/CA3 subregions of the hippocampus. In addition, microglial apoptosis in the early stage of CUS appeared to be involved in microglia loss. Further, the expression of pro-inflammatory cytokines (IL-1β and IL-18) was significantly decreased after CUS. In contrast, the expression of the anti-inflammatory cytokine IL-4 was significantly increased after 2 weeks of CUS. These results suggested that the CUS-induced dynamic changes in hippocampal [18F]DPA-714 uptake and several cytokines may be due to combined microglial and astrocyte action. These findings provide a theoretical reference for the future clinical applications of TSPO PET.